Cardiovascular events observed among patients in the etrasimod clinical programme: an integrated safety analysis of patients with moderately to severely active ulcerative colitis - Xiang Guo; Peter M Irving; Laurent Peyrin-Biroulet; Séverine Vermeire; Joseph Wu; Irene Modesto; David T Rubin; Marla C Dubinsky; Andres J Yarur; Miguel Regueiro; Martina Goetsch; Krisztina Lazin; et al. (BMJ Open Gastroenterology)
Objective Etrasimod is an oral, once-daily, selective sphingosine 1-phosphate (S1P)1,4,5 receptor modulator for the treatment of moderately to severely active ulcerative colitis (UC). S1P1 receptor expression on cardiac cells is involved in cardiac conduction. We report cardiovascular treatment-emergent adverse events (TEAEs) associated with S1P receptor modulators and other cardiovascular events in the etrasimod UC clinical programme.Methods Patients were analysed in the Placebo-controlled UC cohort and All UC cohort. Incidence rates (IRs, per 100 patient-years) of cardiovascular-related TEAEs associated with S1P receptor modulators, including bradycardia/atrioventricular (AV) block and hypertension, and other cardiovascular events, including coronary artery disease (CAD) and cerebrovascular disease (CVD), were analysed.Results In patients receiving etrasimod, cardiovascular-related TEAEs were infrequent (≤2.6% per AE). In the Placebo-controlled UC cohort, IRs (95% CIs) for cardiovascular-related TEAEs were higher for patients receiving etrasimod (n=577) vs placebo (n=314), respectively, for bradycardia/sinus bradycardia, 3.85 (1.58 to 6.13) vs 0 and AV block, 1.40 (0.03 to 2.76) vs 0; and numerically higher for hypertension, 5.31 (2.62 to 7.99) vs 3.40 (0.07 to 6.72). Most bradycardia/AV block events were reported on day 1. All bradycardia and hypertension TEAEs were non-serious. One serious second-degree AV block type 1 TEAE occurred in the etrasimod group; no events of second-degree AV block type 2 or higher were reported. One event each of CAD and CVD occurred in two patients receiving etrasimod.Conclusions In the etrasimod UC clinical programme, IRs of cardiovascular-related TEAEs and other cardiovascular events were low. Most cardiovascular-related TEAEs were non-serious.Trial registration numbers NCT02447302; NCT03945188; NCT03996369; NCT02536404; NCT03950232; NCT04176588.